The occupation as an object and tool: when is the occupation alive? - Marjorie Schliebener Tobar (Cadernos Brasileiros de Terapia Ocupacional, 2020)
This article aims to describe and analyze an understanding of occupation as an object and tool. Based on the constant effort, in occupational therapy, it aims to clarify its theoretical foundations and define its field of action. In this context, the criticism arises that understanding the occupation as an object could lead to a reified notion of human occupational experience, distorting the original horizon of the discipline. Thus, it is concluded, first, how an understanding of occupation as a “thing” leads to understanding it as an inert object and isolated from human experience. Then, secondly, under the pretense of accessing a mode of understanding that allows us to understand the phenomenon of occupation in intimate relationship with the existence of human beings in their daily lives, it is considered, from the thought of Martin Heidegger, the possibility of understanding, in a “live” way, human occupation.